Kisah Al-Qur’an dalam Tinjauan Sains (Studi atas Serial Tafsir Ilmi Kementerian Agama RI) - Faizin Faizin (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This article discusses the pattern of integration of religion and science in the book series Tafsir Ilmi “Kisah Nabi Pra-Ibrahim dalam Perspektif Al-Qur’an dan Sains.” This descriptive-qualitative research uses the quantum integration theory Nidhal Guessoum (2011) through library research. The results of this study show that there are three patterns of integration that are strictly applied in the work. First, the pattern of integration of the story of the Qur'an and science emphasizes the principle that there is no contradiction between the Qur'an and science, both in terms of source, purpose, method, and content. Second, it can be seen that the application of multiple layered interpretation patterns in the work confirms that there is no single truth in explaining the historical information of human civilization. Third, the theological falsification pattern proves the existence of methodological and metaphysical aspects. The methodological aspect shows that there is a valid presentation of scientific data. The metaphysical aspect of the Qur'anic story advocates the internalization of moral-spiritual values for the reader.